Pengaruh Kemampuan Kerja, Kompensasi, Disiplin Kerja dan Pengawasan terhadap Kinerja Karyawan Pada PT. PLN (Persero) UP3 Kota Metro - Sari, Peni Arum; Ratmono, Ratmono (Jurnal Manajemen DIVERSIFIKASI, 2021)
Employee performance is an important aspect in a company. The company strives to find and nurture employees with high enthusiasm, to create and maintain competitive human resources. Human resources are what ultimately become the backbone for the success of a company. The formulation of the problem in this study is "Whether the work ability, compensation, work discipline and supervision simultaneously affect the performance of the employees of PT. PLN (Persero) UP3 Kota Metro ". From these problems, the purpose of this study is to determine the effect of work ability, compensation, work discipline and supervision simultaneously affect the performance of employees of PT. PLN (Persero) UP3 Metro City. This research method is quantitative. The techniques used in data collection in this research are observation, interview, documentary and questionnaire techniques. Then in data analysis using quantitative methods, namely the data collected and then analyzed. After the data is collected, then the data is analyzed using multiple regression analysis and processed using SPSs. Based on data analysis using SSS, the conclusion of this study namely work ability, compensation, work discipline and supervision have a positive and significant effect together on the employee performance of PT PLN (Persero) UP3 Kota Metro.